A Review on the Treatment of Petroleum Sludge and Use as Construction Materials - Nurul Noraziemah Mohd Pauzi; Mohamad Shazwan Ahmad Shah (Civil and Sustainable Urban Engineering, 2022)
Petrochemical is a vital pillar industry for the national economic growth wherein the past few years, it has produced a huge amount of petroleum sludge. Petroleum sludge (PS) contains toxic and carcinogenic-mutagenic compounds and heavy metals, which are a major source of pollution in the environment. Thus, it needs to be properly treated and disposed of. Correspondingly, this paper presents a review of the techniques to treat petroleum waste to effectively immobilize the heavy metals and highlights their possible application as construction materials. This review concludes that each treatment method (i.e., solidification, stabilization, incineration, bioremediation, centrifugation, etc.) has its own merits and demerits and may be more suitable for certain applications than others. The use of pyrolysis, solidification, and stabilization techniques has been demonstrated to be potentially beneficial in protecting the environment from contaminants in PS and further recycling PS as cementitious materials. However, the selection of suitable treatment methods has to be made based on the chemical composition of the waste, method capacity, costs, and disposal standards. Therefore, an overall evaluation is required prior to treatment method selection to ensure the safe disposal or recycling of petroleum waste. This review could improve basic knowledge of PS treatment and disposal techniques and serve as a future guide for recycling PS as a building material.